Analisis Korelasi Warna terhadap Aperture, ISO dan Shutter Speed (Exposure Triangle) Kamera Digital Single Lens Reflex - Ari Wibowo; Happy Yugo Prasetya; Andri Albertha Pratama (JURNAL INTEGRASI, 2015)
When taking a photograph, the camera then adjusts how much light comes in through the DSLR camera lens. The exposure point on the automatic setting is not only determined by the aperture, ISO and shutter speed point alone, but also influenced by the object's response to light, and the distance of camera to the object, the use of certain filter on the camera lens as well as the type and intensity of the light source during the shooting process. This research was conducted by using experimental study. Data collection method used is observation of 10 basic colors. Those colors evenly represent the composition of the RGB and CMYK. Technique of data analysis is correlation. The study resulted the composition of Red, Green and Blue contributed a great influence to shutter speed. Meanwhile, it was found that Red, Green and Blue influence very small to aperture and ISO value wiss constant (there is no influence).